A literature review of school practices to overcome school failure - Faubert, Brenton (OECD publishing, 2012)
This working paper was prepared as part of the OECD thematic review Overcoming School Failure: Policies that Work, www.oecd.org/edu/equity. The project provides evidence on the policies that are effective to reduce school failure by improving low attainment and reducing dropout, and proactively supports countries in promoting reform. The project builds on the conceptual framework developed in the OECD’s No More Failures: Ten Steps to Equity in Education (2007). Austria, Canada (Manitoba, Ontario, Québec and Yukon), Czech Republic, France, Greece, Ireland, Netherlands, Spain and Sweden took part in this project. This working paper is part of a series of papers prepared for the thematic review Overcoming School Failure: Policies that Work covering the topics of policies to reduce dropout and in-school practices to reduce school failure. These report have been used as background material for the final comparative report Equity and Quality in Education: Supporting Disadvantaged Schools and Students (OECD, 2012), which gives evidence on the policy levers that can help overcome school failure and reduce inequities in OECD education systems. It focuses on the reasons why investing in overcoming school failure -early and up to upper secondary- pays off, on alternatives to specific system level policies that are currently hindering equity, and on the actions to be taken at school level, in particular in low performing disadvantaged schools.
Keywords: contenus de l'éducation; difficulté d'apprentissage; politique éducative; système éducatif